Redox-active engineered holey reduced graphene oxide films for K+ storage. (15th April 2021) - Xu, Yali; Fan, Binbin; Liu, Zheng; Huang, Cong; Hu, Aiping; Tang, Qunli; Zhang, Shiying; Deng, Weina; Chen, Xiaohua
Abstract: Graphene film is promising candidate as free-standing electrodes for potassium-ion batteries (KIBs) owing to its intrinsic nature of mechanical strength and high electrical conductivity. However, its performance is usually restricted by the tightly stacked structure and sluggish insertion/deinsertion K storage mechanism. Herein, a redox-active engineered holey reduced graphene oxide (HRGO) film anode was prepared by using the carboxylic acid functionalized polystyrene (PS-COOH) spheres as the template. The holey ion diffusion network channels and the oxygen functional groups can be optimized during the PS-COOH spheres decomposition process, which largely promote the enhancement of electrochemical performance because the oxygen functional groups can serve as the surface-redox sites increasing surface-driven reactions and holey channels provide more ion-accessible area for K-ion storage. Moreover, the reduction degree of graphene oxide also be simply tuned by changing the annealing temperature, which can improve the K + bulk intercalation reaction. As a result, the optimized HRGO-900 (HRGO sample obtained at 900 °C) films exhibits a superior areal capacity (0.80 mAh cm −2 at 0.1 mA cm −2 ). The electrode design and construction strategies can be effectively applied in other 2D materials, which exhibits practical applications in energy storage devices. Graphical abstract: Image 1 Highlights: The film is directly used as an anode without binder and metal current collector. The oxygen functional groups and holey were simultaneously introduced. The influence of reduction degree and oxygen content on K + storage is uncovered.